Anticancer Effects of Extracts from the Fruit of Morinda Citrifolia (Noni) in Breast Cancer Cell Lines - Sharma, K.; Pachauri, S. D.; Khandelwal, K.; Ahmad, H.; Arya, A.; Biala, P.; Agrawal, S.; Pandey, R. R.; Srivastava, A.; Srivastav, A.; Saxena, J. K.; Dwivedi, A. K. (Drug Research, 2016)
Morinda citrifolia L. (NONI) fruits have been used for thousands of years for the treatment of many health problems including cancer, cold, diabetes, flu, hypertension, and pain. Plant extracts have reported several therapeutic benefits, but extraction of individual compound from the extract often exhibits limited clinical utility as the synergistic effect of various natural ingredients gets lost. They generally constitute polyphenols and flavonoids. Studies have suggested that these phytochemicals, especially polyphenols, display high antioxidant properties, which help to reduce the risk of degenerative diseases, such as cancer and cardiovascular diseases. Several in-vitro and in-vivo studies have shown that Noni fruits have antioxidant, anti-inflammatory, anti-dementia, liver-protective, anticancer, analgesic, and immunomodulatory effects. Till date about 7 in vitro cancer studies have been done, but a detailed in vitro study including cell cycle and caspase activation assay on breast cancer cell line has not been done. In the present study different Noni fruit fractions have tested on cancer cell lines MCF-7, MDA-MB-231 (breast adenocarcinoma) and one non-cancer cell line HEK-293 (Human embryonic kidney). Out of which ethylacetate extract showed a higher order of in vitro anticancer activity profile. The ethylacetate extract strongly inhibited the proliferation of MCF-7, MDA-MB-231 and HEK-293 cell lines with IC50 values of 25, 35, 60 µg/ml respectively. The extract showed increase in apoptotic cells in MCF-7 and MDA-MB-231 cells and arrested the cell cycle in the G1/S phase in MCF-7 and G0/G1 phase in MDA-MB-231 cells. Noni extract also decreases the intracellular ROS generation and mitochondrial membrane potential.
Keywords: cancer; cell proliferation; apoptosis